HUMAS SEBAGAI METHOD OF COMMUCATION DALAM MEMBENTUK IMAGE MADRASAH - Abrori, Husnan (JURNAL AL-TANZIM, 2018)
In every public relations institution has a role, because through public relations the strategy plan forms the public opinion of educational service users of an institution both negative and positive opinions. This study aims to determine how the public relations communication strategy in forming a positive public opinion so that the image of the institution becomes good and has an impact on marketable institutions. In this study the authors used a qualitative descriptive approach. The public relations communication strategy in the Public Relations Section of MTs Nurul Yaqin is by implementing two communications, internal communication and external communication. The difficulty in communication strategies in the public relations department of MTs Nurul Yaqin is the quality of human resources who still lack the mastery of communication techniques. To achieve the goal of MTs Nurul Yaqin Public Relations in shaping the image of the institution, it requires team cohesiveness, sincere work, discipline and professionalism in public relations.